Celebrating the 30th anniversary of Edwin E. Gordon's first visit to Portugal: Thank you, Doctor Gordon - Rodrigues, Helena (2025)
The year 2025 marked the thirtieth anniversary of Edwin E. Gordon's (1927–2015) first visit to Portugal. Between 1995 and 2008, the educator, professor, and researcher was a prominent figure at the Calouste Gulbenkian Foundation in Lisbon and at other locations across the country. His research stands out for its unique contribution to the study of musical aptitudes, audiation, music learning theory, tonal and rhythmic patterns, and musical development in infants and young children. He was the author of six musical aptitude tests and numerous books, articles, and research monographs. This publication is a reissue of Helena Rodrigues' article, published after his first visit to Portugal in November 1995, which summarises the information shared in these seminars.